2007
DOI: 10.1016/j.ydbio.2006.11.022
|View full text |Cite
|
Sign up to set email alerts
|

The Notch signaling pathway in the cnidarian Hydra

Abstract: Many of the major pathways that govern early development in higher animals have been identified in cnidarians, including the Wnt, TGFbeta and tyrosine kinase signaling pathways. We show here that Notch signaling is also conserved in these early metazoans. We describe the Hydra Notch receptor (HvNotch) and provide evidence for the conservation of the Notch signaling mode via regulated intramembrane proteolysis. We observed that nuclear translocation of the Notch intracellular domain (NID) was inhibited by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 61 publications
5
79
1
1
Order By: Relevance
“…The two myxozoans and P. hydriforme were also found to have key elements of the Notch-signaling pathway, and M. cerebralis possessed some elements of the TGFβ pathway (Table 4 and Dataset S3). Notch is reported to have an important role in differentiation of stem-cell lineages (50), whereas TGFβ appears to play a more general role in cell signaling (51).…”
Section: Analyses Of Gene Pathways and Candidate Genes In The Transcrmentioning
confidence: 99%
“…The two myxozoans and P. hydriforme were also found to have key elements of the Notch-signaling pathway, and M. cerebralis possessed some elements of the TGFβ pathway (Table 4 and Dataset S3). Notch is reported to have an important role in differentiation of stem-cell lineages (50), whereas TGFβ appears to play a more general role in cell signaling (51).…”
Section: Analyses Of Gene Pathways and Candidate Genes In The Transcrmentioning
confidence: 99%
“…Beyond the ligand (Delta) and receptor (Notch), the proteases that process the Notch preprotein (furin, O-fut and fringe) and liberate the intracellular domain from the extracellular domain (ADAM-type metalloproteases and the g-secretase complex) are critically important for effective signalling. Outside of Bilateria, Notch homologues have been found in cnidarians [27,99], placozoans [11,15], sponges [17] and ctenophores [11,13]. Notch-like proteins have also been described from the choanoflagellate Monosiga brevicollis and the filasterean Capsaspora owczarzaki, though these proteins lack key functional domains including the Delta interaction domain (DSL) in the former and the epidermal growth factor (EGF) domains in both taxa [26].…”
Section: Parahoxozoan Pathways (A) Notch/delta Signallingmentioning
confidence: 99%
“…Notch/Delta signalling pathways are known to be functional in cnidarians and bilaterians but the roles of these pathways may be quite different in these two lineages. Pharmacological studies using the g-secretase inhibitor DAPT have identified a role for Notch/Delta signalling in neural specification across cnidarians [99,104,105], but knockdown experiments in the sea anemone N. vectensis suggest that cnidarians use the non-canonical Notch pathway, independent of the hairy/enhancer of split (HES) transcription factors, in this process [106]. Curiously, cnidarians have orthologues of HES genes (indeed, HES genes are found throughout Metazoa), suggesting that the canonical Notch/HES signalling pathway may be used in a context other than neural specification in non-bilaterian metazoans.…”
Section: Parahoxozoan Pathways (A) Notch/delta Signallingmentioning
confidence: 99%
“…These studies identified the differentiation pathways of most cell types in homeostatic and regenerative conditions. In addition, the molecular work performed over the past 20 years has started to dissect the genetic pathways at work during budding, regeneration and reaggregation as the canonical Wnt pathway for maintaining and re-establishing apical organizer activity [33][34][35][36][37][38][39] , the non-canonical Wnt pathway for cellular evagination processes 38 , the MAPK-CREB pathway for triggering head regeneration 46 , the BMP/chordin pathway for axis patterning 47,48 , the FGF pathway for bud detachment 49 , the Notch pathway for differentiating some interstitial cell lineages 50 .…”
Section: Plasticity Of Regeneration In Hydramentioning
confidence: 99%